2022
DOI: 10.3390/jcm11175031
|View full text |Cite
|
Sign up to set email alerts
|

Motor Coordination and Global Development in Subjects with Down Syndrome: The Influence of Physical Activity

Abstract: Background: Many research studies have investigated motor impairments and delayed development in children with Down Syndrome (DS). However, very few studies detected these features in adults with DS. Hence, this study aimed to investigate the relationship between motor coordination and global development in subjects with DS, including adults. Furthermore, the second aim was to detect any differences in motor coordination and global development as a function of the practice of physical activity (PA) in this pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…BENDI was developed in search of an instrument that allows the evaluation of basic cognitive skills, which may be relevant domains for the development of more complex cognitive skills. The internal structure of BEDI is consistent with what other authors have suggested regarding these domains as relevant to cognitive development in people with DS [81][82][83].…”
Section: Discussionsupporting
confidence: 89%
“…BENDI was developed in search of an instrument that allows the evaluation of basic cognitive skills, which may be relevant domains for the development of more complex cognitive skills. The internal structure of BEDI is consistent with what other authors have suggested regarding these domains as relevant to cognitive development in people with DS [81][82][83].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, a prior research study has shown that triggering CV 12 Zhongwanand ST 36 Zusanliacupoints decreases serum leptin levels which reduces appetite. (16,17) Laser acupuncture at CV 12 Zhongwan have revealed to trigger b-endorphin secretion via the lopioid receptors within the cerebrum, hepatobiliary system, and pancreatic tissue. This enhances insulin secretion that reduces fasting serum glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported a lack of knowledge and expertise in the class management in case of disability, using tools such as physical activity or technology ( Aihie and Uwaoluetan, 2022 ; Nanayakkara, 2022 ; Tarantino et al, 2022 ). Physical activity games could be a good tool for children’s health, considering that children with disability barely practice physical activity and are at more risk of obesity ( Alesi et al, 2022 ; Alghamdi and Alsaigh, 2023 ). Therefore, teachers should be involved in formal and informal training concerning the strategies for adapting physical education games to different disabilities.…”
Section: Discussionmentioning
confidence: 99%